Green Human Capital and Carbon Emissions of Asian Firms - Li , Fangyuan (Flora); Zhang, Weiming (Elaine); Zhang, Yaojia (Zoe) (Wiley, 2025)
This study examines the impact of green human capital on corporate carbon emissions of Asian firms. Using firm-level carbon emission data and job posting data from 2009 to 2020, we find that a higher proportion of green job postings reduces firms' Scope 1 carbon emissions. This relationship holds across different seniority levels (junior and senior) and functional roles (managerial and technical). We leverage the staggered introduction of sustainability master programs to establish causality. Further analysis shows green human capital promotes both green innovation and renewable energy usage. These findings highlight the crucial role of green employees in driving corporate sustainability, offering policy insights for promoting low-carbon workforce strategies.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 7 - Energía asequible y no contaminante; ODS 8 - Trabajo decente y crecimiento económico; ODS 9 - Industria, innovación e infraestructura; ODS 12 - Producción y consumo responsables; ODS 13 - Acción por el clima; ODS 17 - Alianzas para lograr los objetivos; carbon emissions; green occupations; green patents; human capital; renewable energy